High‐mobility group box‐1 and its role in angiogenesis. Issue 4 (22nd January 2014) - Yang, Shuai; Xu, Linxinyu; Yang, Tianshu; Wang, Fang
Abstract : Review of diverse mechanisms by which HMGB1 regulates angiogenesis, and its involvement in angiogenesisrelated conditions. Abstract : HMGB1 is an architectural chromatin‐binding protein that can be released actively by activated cells or passively by dying cells and can serve as a DAMP molecule to drive the pathogenesis of inflammatory and angiogenic diseases. Through TLR4 and RAGE signaling pathways, HMGB1 could regulate vascular growth in vivo and in vitro through diverse mechanisms, including induction of proangiogenic cytokine release and activation of ECs, macrophages, EPCs, and mesoangioblasts, all of which could contribute to vessel formation. Accordingly, HMGB1 plays a significant role in many angiogenesis‐related conditions, such as tumors, PDR, wound‐healing, and ischemia‐induced angiogenesis. In this review, we focus on the regulatory role of HMGB1 in angiogenesis and recent progress in therapeutic strategies targeting HMGB1.